Zero band gap platinum-based catalysts, methods of preparation and use thereof
Patent Information
- Application Number
- CN202311220745.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-09-20
AI Technical Summary
[0002]质子交换膜电解槽技术在阳极端的催化剂表面实现析氧反应,但阳极端催化剂面临着高酸性和高氧化态环境,会导致催化剂发生高度氧化而析出
[0022]基于上述技术方案,本公开提供的零带隙铂基催化剂、制备方法及其应用,至少包括以下有益效果之一:
Smart Images

Figure CN117512655B_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to the field of catalyst technology, and in particular to a zero-bandgap platinum-based catalyst, its preparation method, and its application. Background Technology
[0002] Proton exchange membrane electrolyzers (PEMECs) enable the oxygen evolution reaction (OER) on the catalyst surface at the anode. However, the anode catalyst faces a highly acidic and oxidized environment, leading to significant oxidation and OER evolution. Commonly used OER catalysts in PEMECs are ruthenium-based and iridium-based materials. Ruthenium-based catalysts exhibit high activity in the oxidized state, but suffer from poor stability in acidic environments. Iridium, on the other hand, is scarce and expensive in the Earth's crust, limiting its large-scale application in the OER. Therefore, developing inexpensive catalysts with high activity and stability is a crucial research direction for advancing the large-scale preparation of OER catalysts. Summary of the Invention
[0003] To address the aforementioned technical problems, this disclosure provides a zero-bandgap platinum-based catalyst, its preparation method, and its application, aiming to at least partially solve the technical problems mentioned above.
[0004] To solve the above-mentioned technical problems, the technical solution provided in this disclosure is as follows:
[0005] As a first aspect of this disclosure, a method for preparing a zero-bandgap platinum-based catalyst is provided, comprising:
[0006] Platinum salt, ammonia water, and a dispersant are added to water to form a platinum-ammonia complex with platinum ions, resulting in a mixed solution.
[0007] Adding doped metal salts and / or boron salts to the mixed solution allows the doped metal ions and / or boron ions to mix and coordinate with the platinum-ammonia complex, resulting in a transparent solution.
[0008] A transparent solution was rotary evaporated, and the resulting powder was annealed to obtain a zero-bandgap platinum-based catalyst.
[0009] According to embodiments of this disclosure, the platinum salt includes any one or more of chloroplatinic acid, platinum nitrate, potassium chloroplatinate, or sodium chloroplatinate.
[0010] According to embodiments of this disclosure, the dispersant includes any one or more of nitrates, potassium bromide, oxalic acid, and citric acid;
[0011] Nitrates include any one or more of potassium nitrate, sodium nitrate, or zinc nitrate.
[0012] According to embodiments of this disclosure, the mass ratio of platinum salt to water is 0.01:100 to 5:100;
[0013] The molar concentration of ammonia water is 1~10 mol / L.
[0014] According to embodiments of this disclosure, the molar ratio of platinum in the platinum salt to the doped metal in the doped metal salt is 1:0.5 to 1:2;
[0015] The molar ratio of platinum in platinum salts to boron in boron salts is 1:0.01 to 1:2.
[0016] According to embodiments of this disclosure, the boron salt includes any one or more of boron oxide, boric acid, or sodium tetraborate;
[0017] The doped metal salts include any one or more of strontium salts, chromium salts, tungsten salts, and manganese salts, wherein the strontium salts include any one or more of strontium nitrate, strontium chloride, or strontium acetate.
[0018] According to embodiments of this disclosure, the annealing temperature is 400~700℃, the heating rate is 1~10℃ / min, and the annealing time is 1~12 h.
[0019] According to embodiments of this disclosure, the zero-bandgap platinum-based catalyst obtained after annealing is washed with deionized water to remove residual soluble salts in the zero-bandgap platinum-based catalyst.
[0020] As a second aspect of this disclosure, a zero-bandgap platinum-based catalyst is provided, prepared using the above-described preparation method.
[0021] As a third aspect of this disclosure, the application of a zero-bandgap platinum-based catalyst in oxygen evolution through water electrolysis is provided.
[0022] Based on the above technical solution, the zero-bandgap platinum-based catalyst, preparation method, and application provided in this disclosure have at least one of the following beneficial effects:
[0023] (1) In the embodiments of this disclosure, the doped metal salt and / or boron salt added to the mixed solution has the effect of adjusting the band gap of platinum oxide. Under the high temperature of the annealing process, an intermediate energy level can be introduced into the electronic structure of platinum oxide, promoting the transfer of electrons in platinum oxide from the valence band to the conduction band, thereby forming a zero band gap platinum-based catalyst with a band gap of zero.
[0024] (2) In the embodiments of this disclosure, the band gap of the zero band gap platinum-based catalyst is zero, and electrons can migrate rapidly between the catalyst surface and the oxygen-containing intermediate, thereby enhancing the intrinsic activity of the platinum-based catalyst, so that the platinum-based catalyst can be used in acidic and high oxidation states and exhibits high stability and electrical conductivity.
[0025] (3) In the embodiments of this disclosure, the addition of platinum salt and ammonia water to form a mixed solution allows platinum ions and ammonia to form a platinum-ammonia complex, which can exist stably in a polar environment and has high stability. This avoids changes in platinum salt under acidic or alkaline conditions, which would affect the catalytic activity of platinum. Furthermore, the addition of a dispersant to form a mixed solution prevents the complex from agglomerating, allowing the platinum-ammonia complex and the doped metal and / or boron salt to be uniformly dispersed in a transparent solution. This results in a uniformly mixed powder after rotary evaporation, thereby obtaining a platinum-based catalyst with a uniform texture. Attached Figure Description
[0026] Figure 1 This is an optical photograph of the zero-bandgap platinum-based catalyst in Example 1 of this disclosure;
[0027] Figure 2 Electrochemical impedance spectroscopy of the zero-bandgap platinum-based catalyst in Example 1 of this disclosure;
[0028] Figure 3 Linear voltammetry curves of the zero-bandgap platinum-based catalyst in Example 1 of this disclosure;
[0029] Figure 4 This is an optical photograph of the zero-bandgap platinum-based catalyst in Example 2 of this disclosure;
[0030] Figure 5 Electrochemical impedance spectroscopy of the zero-bandgap platinum-based catalyst in Example 2 of this disclosure;
[0031] Figure 6 The linear voltammetric curves of the zero-bandgap platinum-based catalyst in Example 2 of this disclosure are shown. Detailed Implementation
[0032] To make the objectives, technical solutions, and advantages of this disclosure clearer, the following detailed description is provided in conjunction with specific embodiments and the accompanying drawings.
[0033] The embodiments of the present disclosure will now be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the disclosure. In the following detailed description, numerous specific details are set forth to provide a thorough understanding of the embodiments of the present disclosure for ease of explanation. However, it will be apparent that one or more embodiments may be practiced without these specific details. Furthermore, descriptions of well-known structures and techniques are omitted in the following description to avoid unnecessarily obscuring the concepts of the present disclosure.
[0034] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit this disclosure. The terms “comprising,” “including,” etc., as used herein indicate the presence of features, steps, operations, and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, or components.
[0035] All terms used herein (including technical and scientific terms) have the meanings commonly understood by those skilled in the art, unless otherwise defined. It should be noted that the terms used herein are to be interpreted in a manner consistent with the context of this specification, and not in an idealized or overly rigid way.
[0036] When using expressions such as "at least one of A, B, and C," the expression should generally be interpreted in accordance with the meaning commonly understood by a person skilled in the art (e.g., "a system having at least one of A, B, and C" should include, but is not limited to, systems having A alone, having B alone, having C alone, having A and B, having A and C, having B and C, and / or having A, B, and C, etc.). When using expressions such as "at least one of A, B, or C," the expression should generally be interpreted in accordance with the meaning commonly understood by a person skilled in the art (e.g., "a system having at least one of A, B, or C" should include, but is not limited to, systems having A alone, having B alone, having C alone, having A and B, having A and C, having B and C, and / or having A, B, and C, etc.).
[0037] In the process of developing this disclosure, it was discovered that platinum group metals, including platinum (Pt), palladium (Pd), osmium (Os), iridium (Ir), ruthenium (Ru), and rhodium (Rh), are commonly used catalytic materials for water splitting in acidic solutions. In acidic solutions, the oxygen evolution activity of platinum group metals follows the order: Ru > Ir > Rh > Pd > Pt; the structural stability order is: Pd > Pt > Rh > Ir > Ru. Considering catalytic activity, stability, and cost, platinum shows promise for application in the oxygen evolution reaction (OER) to achieve large-scale preparation of highly active OER catalysts. However, platinum metal forms an oxide layer on its surface under high potential conditions. These oxide layers are electronically insulating, which hinders electron transfer during the OER process, thus continuously reducing the OER activity of platinum-based catalysts.
[0038] Current research on the influence of platinum oxide layer thickness on oxygen evolution activity reveals that within the oxygen evolution potential range, the Tafel slope of platinum catalysts is greater than 120 mV / dec, indicating that the platinum oxide layer restricts charge transfer, which is detrimental to the high oxygen evolution activity exhibited by metallic platinum catalysts. Testing the Tafel slopes of bulk platinum and nano-platinum under acidic conditions (145 and 210 mV / dec, respectively) shows that due to the thick oxide layer formed on the surface of nano-platinum, the charge transport resistance of platinum nanoparticles is relatively high during oxygen evolution, exhibiting lower intrinsic activity. Furthermore, platinum oxide materials are thermodynamically unstable, and continuous transformation between platinum oxide and platinum occurs during cyclic voltammetry scans, severely affecting the lifespan and catalytic activity of platinum catalysts.
[0039] Therefore, the preparation of platinum-based catalysts with zero band gap is an important research topic for improving the conductivity of platinum-based catalysts and promoting electron transport during the oxygen evolution reaction.
[0040] In view of the technical problems existing in related technologies, this disclosure provides a zero-bandgap platinum-based catalyst, its preparation method, and its application. The catalyst is prepared by forming a platinum-ammonia complex with platinum ions using a solution method, while adding a dispersant to prevent solute aggregation. Furthermore, it utilizes doped metal salts and / or boron salts to coordinate with platinum ions, followed by annealing to obtain a homogeneous zero-bandgap platinum-based catalyst. This effectively improves conductivity and allows for use under high acidity and high oxidation states, making it suitable for proton exchange membrane electrolyzers to achieve the oxygen evolution reaction at the anode. The preparation method is simple, reproducible, and uses low-cost reagents, making it suitable for large-scale industrial production and showing promising application prospects.
[0041] Specifically, as a first aspect of this disclosure, a method for preparing a zero-bandgap platinum-based catalyst is provided, comprising:
[0042] Platinum salt, ammonia, and a dispersant are added to water to form a platinum-ammonia complex with platinum ions, resulting in a mixed solution. A doped metal salt and / or boron salt are then added to the mixed solution to allow the doped metal ions and / or boron ions to mix and coordinate with the platinum-ammonia complex, resulting in a transparent solution. The transparent solution is then subjected to rotary evaporation, and the powder obtained after rotary evaporation is annealed to obtain a zero-bandgap platinum-based catalyst.
[0043] According to embodiments of this disclosure, platinum salt, ammonia, and dispersant can be added to the aqueous solution sequentially or simultaneously for mixing. A stable platinum-ammonia complex is formed by platinum ions and ammonia, preventing changes in the platinum salt under acidic or alkaline conditions. The dispersant forms a uniformly dispersed mixed solution, preventing aggregation of the complex. Subsequently, doped metal salts and / or boron salts are added to the mixed solution for coordination to form a transparent solution. Water and ammonia are removed by rotary evaporation to form a uniformly mixed catalyst precursor powder, which is then annealed to obtain a zero-bandgap platinum-based catalyst.
[0044] According to embodiments of this disclosure, the doped metal salt and / or boron salt has the effect of regulating the band gap of platinum oxide. Platinum oxide is formed under the high temperature of the annealing process. The doped metal salt and / or boron salt introduce intermediate energy levels into the electronic structure of platinum oxide, promoting the transfer of electrons in platinum oxide from the valence band to the conduction band, thereby forming a zero-bandgap platinum-based catalyst with a band gap of zero.
[0045] According to embodiments of this disclosure, the platinum salt includes any one or more of chloroplatinic acid, platinum nitrate, potassium chloroplatinate, or sodium chloroplatinate. The mass ratio of the platinum salt to water is 0.01:1000 to 5:1000, for example, 0.01:1000, 0.15:1000, 1.25:1000, 2.5:1000, 4.55:1000, etc., but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0046] According to the embodiments of this disclosure, the molar concentration of ammonia water is 1~10 mol / L, for example, it can be 1 mol / L, 3 mol / L, 5 mol / L, 7 mol / L, 9 mol / L, etc., but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0047] According to embodiments of this disclosure, the dispersant includes any one or more of nitrates, potassium bromide, oxalic acid, and citric acid; wherein the nitrate includes any one or more of potassium nitrate, sodium nitrate, or zinc nitrate.
[0048] According to embodiments of this disclosure, by adding a dispersant, the substances can be fully mixed after the addition of doped metal salts and / or boron salts, resulting in a uniformly dispersed transparent solution. This leads to a uniformly mixed catalyst precursor powder, which is then annealed to fully react and obtain a platinum-based catalyst with a uniform texture.
[0049] According to embodiments of this disclosure, the molar ratio of platinum to the doped metal is 1:0.1 to 1:10, for example, it can be 1:0.1, 1:1, 1:3, 1:5, 1:7, etc.; the molar ratio of platinum to boron is 1:0.01 to 1:10, for example, it can be 1:0.05, 1:2.98, 1:6.25, 1:7.85, 1:9, etc. However, it is not limited to the listed values, and other unlisted values within this range are also applicable.
[0050] According to embodiments of this disclosure, the addition ratios of platinum salt to doped metal salt and platinum salt to boron salt need to be adjusted based on the aforementioned molar ratios of platinum to doped metal and platinum to boron. If the amount of doped metal salt added is too small, it will be difficult to function effectively, making bandgap adjustment challenging; if the amount of boron salt added is too small, it will lead to decreased catalyst activity; if the amount of boron salt added is too large, it will decrease the catalyst's conductivity.
[0051] According to embodiments of this disclosure, the boron salt includes any one or more of boron oxide, boric acid, or sodium tetraborate; the doped metal salt includes any one or more of strontium salt, chromium salt, tungsten salt, and manganese salt, wherein the strontium salt includes any one or more of strontium nitrate, strontium chloride, or strontium acetate.
[0052] According to embodiments of this disclosure, the doped metal salt is preferably a strontium salt, and more preferably, a strontium salt and a boron salt are added to the mixed solution. The boron salt plays a dominant role in promoting the formation of a zero bandgap in platinum oxide, and can also be used alone for bandgap adjustment.
[0053] According to embodiments of this disclosure, the annealing process is carried out in air. During the annealing process, platinum salts are oxidized to platinum oxide. Doping with metal salts and boron salts at high temperatures modulates the electronic structure of platinum oxide, promoting the formation of a zero band gap. The annealing temperature is 400~700℃, for example, 410℃, 480℃, 520℃, 570℃, 630℃, etc.; the heating rate is 1~10℃ / min, for example, 1℃ / min, 3℃ / min, 5℃ / min, 7℃ / min, 9℃ / min, etc.; and the annealing time is 1~12 h, for example, 2 h, 4 h, 6 h, 9 h, 10 h, etc. However, it is not limited to the listed values; other unlisted values within this range are also applicable.
[0054] According to embodiments of this disclosure, the zero-bandgap platinum-based catalyst obtained after annealing is washed with deionized water to remove residual soluble salts in the zero-bandgap platinum-based catalyst.
[0055] According to the embodiments of this disclosure, the zero-bandgap platinum-based catalyst obtained after annealing may have impurities attached to it, and there may be residual soluble salts on the catalyst surface, such as borates, strontium salts, platinum salts, etc. Deionized water can be used to clean it to remove impurities and soluble salts, and then it can be dried to obtain the target catalyst, namely the zero-bandgap platinum-based catalyst.
[0056] As a second aspect of this disclosure, a zero-bandgap platinum-based catalyst is provided, prepared using the above-described preparation method.
[0057] According to embodiments of this disclosure, the zero-bandgap platinum-based catalyst appears as a black solid powder with low charge transport resistance.
[0058] As a third aspect of this disclosure, the application of a zero-bandgap platinum-based catalyst in oxygen evolution through water electrolysis is provided.
[0059] According to embodiments of this disclosure, the provided zero-bandgap platinum-based catalyst has a zero bandgap, allowing electrons to migrate rapidly between the catalyst surface and the oxygen-containing intermediate, thereby enhancing the intrinsic activity of the platinum-based catalyst and exhibiting high electrical conductivity. The zero-bandgap platinum-based catalyst demonstrates extremely fast charge transfer rates and high activity in catalytic experiments of oxygen evolution through water electrolysis, facilitating the oxygen evolution process and solving the problems of high cost and poor stability of ruthenium-based and iridium-based catalysts in existing proton exchange membrane water electrolysis hydrogen production anodes.
[0060] To make the objectives, technical solutions, and advantages of this disclosure clearer, the technical solutions and principles of this disclosure are further illustrated below with reference to specific embodiments and accompanying drawings. It should be noted that the specific embodiments described below are merely illustrative examples, and the scope of protection of this disclosure is not limited thereto.
[0061] Unless otherwise specified, all test materials and reagents used in the following examples are commercially available. Methods not specifically described in the examples are conventional and can be performed according to the techniques or conditions described in the literature or the product instructions.
[0062] Example 1
[0063] At room temperature, 100 mg of chloroplatinic acid hexahydrate was added to 100 ml of solution, and the platinum salt was dispersed evenly using magnetic stirring. Then, 20 ml of 5 mol / L ammonia solution was slowly added, and stirring was continued for 6 h to form a platinum-ammonia complex. 500 mg of citric acid was then added and stirred for 2 h to obtain a mixed solution. 306 mg of strontium chloride and 72 mg of sodium borate were added to the mixed solution, and stirring was continued for 2 h to form a uniformly dispersed transparent solution. The transparent solution was then subjected to rotary evaporation to obtain a solid powder, which was annealed at 600 °C for 6 h. After washing with water and drying, a zero-bandgap platinum-based catalyst was obtained, labeled as B-SrPtO3 catalyst.
[0064] The zero-bandgap platinum-based catalyst prepared in Example 1 of this disclosure was observed, such as... Figure 1 As shown, Figure 1 The image shown is an optical photograph of the zero-bandgap platinum-based catalyst in Example 1 of this disclosure. It can be seen that the zero-bandgap platinum-based catalyst has a black appearance and high light absorption.
[0065] Furthermore, the zero-bandgap platinum-based catalyst of Example 1 was subjected to electrochemical impedance spectroscopy and electrochemical linear voltammetry.
[0066] Figure 2 The electrochemical impedance spectroscopy of the zero-bandgap platinum-based catalyst in Example 1 of this disclosure is shown below. Figure 2 As shown, the magnitude of the fitted impedance in the low-frequency region reflects the ease with which charge transfers and diffuses within the catalyst during the reaction process. Analysis Figure 2 It can be seen that the zero-bandgap platinum-based catalyst prepared in Example 1 has a charge transport resistance of about 30Ω, and it can exhibit a relatively fast charge transfer rate during the catalytic process.
[0067] Figure 3 The linear voltammetric curve of the zero-bandgap platinum-based catalyst in Example 1 of this disclosure shows that the magnitude of the overpotential reflects the catalytic activity of the catalyst in the oxygen evolution reaction. Figure 3It can be seen that the zero-bandgap platinum-based catalyst prepared in Example 1 of this disclosure has an overpotential of 364 mV at a current density of 10 mA·cm-2, and exhibits high catalytic activity in the oxygen evolution reaction.
[0068] Example 2
[0069] The same preparation method as in Example 1 was used, except that 306 mg of strontium chloride and 72 mg of sodium borate were replaced with only 306 mg of strontium chloride. The resulting zero-bandgap platinum-based catalyst was labeled as the SrPtO3 catalyst.
[0070] The appearance of the zero-bandgap platinum-based catalyst prepared in Example 2 of this disclosure was observed, such as... Figure 4 As shown, Figure 4 The image shown is an optical photograph of the zero-bandgap platinum-based catalyst in Example 2 of this disclosure. It can be seen that the zero-bandgap platinum-based catalyst has a gray appearance.
[0071] Furthermore, electrochemical impedance spectroscopy was performed on the zero-bandgap platinum-based catalyst of Example 2. Figure 5 The impedance spectrum of the zero-bandgap platinum-based catalyst in Example 2 of this disclosure is shown below. Figure 5 As shown, the charge transport resistance of the zero-bandgap platinum-based catalyst prepared in Example 2 is approximately 101 Ω.
[0072] Electrochemical linear voltammetry was performed on the zero-bandgap platinum-based catalyst of Example 2, and the results are as follows: Figure 6 As shown, Figure 6 The linear voltammetric curve of the zero-bandgap platinum-based catalyst in Example 2 of this disclosure is shown below. Figure 6 It can be seen that the zero-bandgap platinum-based catalyst prepared in Example 2 of this disclosure has low catalytic activity.
[0073] Example 3
[0074] The same preparation method as in Example 1 was used, except that the annealing temperature was adjusted from 600°C to 700°C.
[0075] The zero-bandgap platinum-based catalyst obtained in Example 3 of this disclosure has the same appearance as the zero-bandgap platinum-based catalyst in Example 1, both exhibiting a black color and high light absorption. Its charge transfer resistance is approximately 64 Ω, and its overpotential is approximately 397 mV, which is slightly higher than that of the zero-bandgap platinum-based catalyst prepared in Example 1.
[0076] Example 4
[0077] The same preparation method as in Example 1 was used, except that the annealing temperature was adjusted from 600°C to 500°C.
[0078] The zero-bandgap platinum-based catalyst obtained in Example 4 of this disclosure has the same appearance as the zero-bandgap platinum-based catalyst in Example 1, both exhibiting a black color and high light absorption. Its charge transfer resistance is approximately 58 Ω and its overpotential is approximately 412 mV, which is slightly higher than that of the zero-bandgap platinum-based catalyst prepared in Example 1.
[0079] Example 5
[0080] The same preparation method as in Example 1 was used, except that 500 mg of citric acid was replaced with 500 mg of sodium nitrate.
[0081] The zero-bandgap platinum-based catalyst obtained in Example 5 of this disclosure has the same appearance as the zero-bandgap platinum-based catalyst in Example 1, both exhibiting a black color and high light absorption. Its charge transfer resistance is approximately 84 Ω, and its overpotential is approximately 386 mV, which is slightly higher than that of the zero-bandgap platinum-based catalyst prepared in Example 1.
[0082] Example 6
[0083] The same preparation method as in Example 1 was used, except that 500 mg of citric acid was replaced with 500 mg of potassium bromide.
[0084] The zero-bandgap platinum-based catalyst obtained in Example 6 of this disclosure has the same appearance as the zero-bandgap platinum-based catalyst in Example 1, both exhibiting a black color and high light absorption. Its charge transfer resistance is approximately 513 Ω and its overpotential is approximately 891 mV, which is much higher than that of the zero-bandgap platinum-based catalyst prepared in Example 1.
[0085] Example 7
[0086] The same preparation method as in Example 1 was used, except that 72 mg of sodium borate was replaced with 36 mg of sodium borate.
[0087] The zero-bandgap platinum-based catalyst obtained in Example 7 of this disclosure has the same appearance as the zero-bandgap platinum-based catalyst in Example 1, both exhibiting a black color and high light absorption. Its charge transfer resistance is approximately 94 Ω, and its overpotential is approximately 405 mV, which is slightly higher than that of the zero-bandgap platinum-based catalyst prepared in Example 1.
[0088] Example 8
[0089] The same preparation method as in Example 1 was used, except that 72 mg of sodium borate was replaced with 18 mg of sodium borate.
[0090] The zero-bandgap platinum-based catalyst obtained in Example 8 of this disclosure has the same appearance as the zero-bandgap platinum-based catalyst in Example 1, both exhibiting a black color and high light absorption. Its charge transfer resistance is approximately 105 Ω, and its overpotential is approximately 437 mV, which is slightly higher than that of the zero-bandgap platinum-based catalyst prepared in Example 1.
[0091] Example 9
[0092] The same preparation method as in Example 1 was used, except that 306 mg of strontium chloride and 72 mg of sodium borate were replaced with only 72 mg of sodium borate. The resulting zero-bandgap platinum-based catalyst was labeled as the PtBO3 catalyst.
[0093] The zero-bandgap platinum-based catalyst obtained in Example 9 of this disclosure has the same appearance as the zero-bandgap platinum-based catalyst in Example 1, both exhibiting a black color and high light absorption. Its charge transport resistance is approximately 27 Ω and its overpotential is approximately 427 mV.
[0094] As can be seen from the above embodiments, the preparation method of the zero-bandgap platinum-based catalyst provided in this disclosure is relatively simple, has a short preparation cycle, the required reactants are easy to obtain and the equipment requirements are low, and the prepared zero-bandgap platinum-based catalyst has the characteristics of phase uniformity and high conductivity, and can achieve high activity and stability. It reduces the preparation cost of the catalyst on the basis of high-activity oxygen evolution reaction and is suitable for large-scale preparation.
[0095] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of this application. It should be understood that the above descriptions are merely specific embodiments of this application and are not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A method for preparing a zero-bandgap platinum-based catalyst suitable for the oxygen evolution reaction in water electrolysis, comprising: Platinum salt, ammonia water, and a dispersant are added to water to form a platinum-ammonia complex with platinum ions, resulting in a mixed solution. Adding doped metal salts and boron salts to the mixed solution allows the doped metal ions and boron ions to mix and coordinate with the platinum-ammonia complex, resulting in a transparent solution. The transparent solution was subjected to rotary evaporation, and the powder obtained after rotary evaporation was annealed to obtain a zero-bandgap platinum-based catalyst. The dispersant includes any one or more of nitrates and citric acid; the nitrate includes any one or more of potassium nitrate, sodium nitrate, or zinc nitrate. The molar ratio of platinum in the platinum salt to the doped metal in the doped metal salt is 1:0.5 to 1:2; the molar ratio of platinum in the platinum salt to boron in the boron salt is 1:0.01 to 1:2; the molar ratio of the doped metal salt to the boron salt is 5.4:1 to 21.6:
1. The boron salt includes any one or more of boron oxide, boric acid, or sodium tetraborate; the doped metal salt is selected from strontium salts, wherein the strontium salt includes any one or more of strontium nitrate, strontium chloride, or strontium acetate; The annealing process is carried out at a temperature of 400~700 ℃, a heating rate of 1~10 ℃ / min, and an annealing time of 1~12 h.
2. The preparation method according to claim 1, wherein, The platinum salt includes any one or more of chloroplatinic acid, platinum nitrate, potassium chloroplatinate, or sodium chloroplatinate.
3. The preparation method according to claim 1, wherein, The mass ratio of the platinum salt to water is 0.01:100 to 5:100; The molar concentration of the ammonia water is 1~10 mol / L.
4. The preparation method according to claim 1 further includes: The zero-bandgap platinum-based catalyst obtained after the annealing treatment is washed with deionized water to remove residual soluble salts from the zero-bandgap platinum-based catalyst.
5. A zero-bandgap platinum-based catalyst, prepared by the method described in any one of claims 1 to 4.
6. The application of a zero-bandgap platinum-based catalyst as described in claim 5 in oxygen evolution by water electrolysis.
Citation Information
Patent Citations
Metal platinum black nanocluster catalyst and preparation method thereof
CN110124664A